Harrison's principles of internal medicine - Eugene, Braunwald; Harrison, Tinsley Randolph, 1900-1978.; Braunwald, Eugene, 1929- (McGraw-Hill, 1987)
Thoroughly revised content—covering the many new breakthroughs and advances in clinical medicine that have occurred since the last edition of Harrison’s. Chapters on acute and chronic hepatitis, management of diabetes, immune-based therapies in cancer, multiple sclerosis, cardiovascular disease, HIV, and many more, deliver the very latest information on disease mechanisms, diagnostic options, and the specific treatment guidance you need to provide optimal patient care. State-of-the-art coverage of disease mechanisms: Harrison’s focuses on pathophysiology with rigor, and with the goal of linking disease mechanisms to treatments. Improved understanding of how diseases develop and progress not only promotes better decision-making and higher value care, but also makes for fascinating reading and improved retention. Harrison’s summarizes important new basic science developments, such as the role of mitochondria in programmed and necrotic cell death, the immune system’s role in cancer development and treatment, the impact of telomere shortening in the aging and disease processes, and the role of the microbiome in health and disease. Understanding the role of inflammation in cardiovascular disease, the precise mechanisms of immune deficiency in HIV/AIDS, prions and misfolded proteins in neurodegenerative diseases, and obesity as a predisposition to diabetes are just a few examples of how this edition provides essential pathophysiology information for health professionals. All-new sections covering a wide range of new and emerging areas of vital interest to all healthcare professionals. New sections include: Sex and Gender-based Issues in Medicine; Obesity, Diabetes Mellitus, and Metabolic Syndrome; and Consultative Medicine—Plus, a new Part covering cutting-edge topics in research and clinical medicine includes great new chapters on the role of Epigenetics in Health and Disease, Behavioral Strategies to Improve Health, Genomics and Infectious Diseases, Emerging Neuro-Therapeutic Technologies, and Telomere Function in Health and Disease, and Network System Medicine. Important and timely new chapters—such as Promoting Good Health, LGBT Health, Systems of Healthcare, Approach to Medical Consultation, Pharmacogenomics, Antimicrobial Resistance, Worldwide Changes in Patterns of Infectious Diseases, Neuromyelitis Optica, and more—offer the very latest, definitive perspectives on must-know topics in medical education and practice. Updated clinical guidelines, expert opinions, and treatment approaches from world-renowned editors and authors contribute to the accuracy and immediacy of the text material and present a clear blueprint for optimizing patient outcomes. End-of-chapter suggested readings reinforce the text material and provide a robust platform for further study and research.